2018
DOI: 10.1101/309708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The histone chaperone FACT modulates nucleosome structure by tethering its components

Abstract: Human FACT (hFACT) is a conserved histone chaperone that was originally described as a transcription elongation factor with potential nucleosome assembly functions. Here we show that FACT facilitates tetrasome assembly and H2A-H2B deposition to form hexasomes and nucleosomes. In the process, FACT tethers components of the nucleosome through interactions with H2A-H2B, resulting in a defined intermediate complex comprised of FACT, a histone hexamer and DNA. Free DNA extending from the tetrasome then competes FAC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…Our current model of FACT function is consistent with published structural studies that showed that mammalian FACT could only bind nucleosomal components or partially disassembled nucleosomes (e.g., lacking the H2A/H2B dimer) because the FACT binding epitopes are hidden within the folded nucleosome (Tsunaka et al 2016;Safina et al 2017;Wang et al 2018). It is also consistent with studies in yeast that showed that FACT is targeted to transcribed chromatin through its recognition of RNA polymerase-disrupted nucleosomes (Martin et al 2018) If the above model is correct, why is transcription increased following the loss of FACT?…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our current model of FACT function is consistent with published structural studies that showed that mammalian FACT could only bind nucleosomal components or partially disassembled nucleosomes (e.g., lacking the H2A/H2B dimer) because the FACT binding epitopes are hidden within the folded nucleosome (Tsunaka et al 2016;Safina et al 2017;Wang et al 2018). It is also consistent with studies in yeast that showed that FACT is targeted to transcribed chromatin through its recognition of RNA polymerase-disrupted nucleosomes (Martin et al 2018) If the above model is correct, why is transcription increased following the loss of FACT?…”
Section: Discussionsupporting
confidence: 89%
“…Several groups recently reported that mammalian FACT could not bind the folded nucleosome (Tsunaka et al 2016;Safina et al 2017;Wang et al 2018), which makes it difficult to explain how FACT can remove the nucleosomal barrier for transcription and replication. However, FACT can bind destabilized nucleosomes or nucleosomes with unwrapped DNA, which was shown in cells and cell-free systems (Tsunaka et al 2016;Safina et al 2017;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural changes that occur in canonical nucleosomes upon FACT binding are likely key to addressing this question, as the observed stimulation is specific to nucleosomal substrates. FACT can reorganize the nucleosome by disrupting histone/DNA contacts, leaving the nucleosome in an "open" or "destabilized" state (Chen et al, 2018;Kemble et al, 2015;McCullough et al, 2011) and by fully displacing H2A/H2B heterodimers (Belotserkovskaya et al, 2003;Chen et al, 2018;Hsieh et al, 2013;Orphanides et al, 1999;Wang et al, 2018;Xin et al, 2009a). The most straightforward explanation for the effect of FACT on Ubp10 activity is that FACT increases H2B deubiquitination by evicting H2A/H2B-Ub heterodimers, which are an excellent substrate for Ubp10 (Figures 2A and 3C).…”
Section: Discussionmentioning
confidence: 99%
“…FACT can remove one H2A-H2B dimer during reorganization and deposit it onto the H3-H4 tetramer or nucleosome hexamer in vitro [184,185]. A recent study demonstrated that FACT itself could not disassemble nucleosomes in vitro [186]. Moreover, DNA replication initiation was delayed when the FACT-MCM2-7 interaction was disrupted [173].…”
Section: Mcm2: Vanguard Of Nucleosome Disassembly and Parental Histonmentioning
confidence: 99%